KATEKESE MULTISENSORIK: TEROBOSAN KATEKETIK BAGI INSAN BERIMAN DIGITAL DEWASA INI - Andalas, Mutiara (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
This research paper proposes a multisensory catechesis as a catechetical breakthrough for digital believer today. Multisensory catechesis is indebted to digital learner autobiographies that encourage the autobiographical exploration of the Church in catechesis. Fulfilling her call as a catechist of the gospel, the Church activates hearing, sighting and touching sensories to communicate the joy of the gospel. The activation of the multisensory of the faithful generation of now refreshes the dialogue between the Gospel and culture in the digital era. This article